RGEC Sebagai Metode Analisis Kesehatan Bank (Studi Kasus Pt Bpr Pijer Podi Kekelengen) - Hutagalung, Cindy Ruth Putri Angelia; Nurlinda, Nurlinda (Universitas Medan Area, 2024)
This Final Report is entitled